Получение эффективных катодолюминесцентных структур на базе пленочной технологии - Kovalenko, L. F.; Sevastjanov, V. V.; Khomchenko, V. S.; Tzyrkunov, Yu. A. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
A technological route has been developed and process parameters have been selected for the serial production of thin-film cathodoluminescent structures used in high-resolution information display devices. Cathodoluminescent structures with a brightness of up to 1000 cd/m² on films with a thickness of 7–9 µm have been obtained and experimentally investigated.